Analyzing the Impact of Economic Performance on the Interplay between Financial Management Strategies and Profitability in the Iraqi Context - AL-Hashimy, Hisham Noori Hussain; Jinfang , Yao (The International Journal of Accounting and Business Society, 2024)
Purpose - This study examines how economic performance affects financial management approaches and profitability in Iraq's construction business. This research examines how financial management strategies affect profitability and economic success. Design/Methodology/Approach—Construction project and site managers in Iraq were surveyed online for the study. Given the scope and magnitude of the research, this study's 85.3% response rate is impressive. In-depth statistical analysis was performed using Partial Least Squares Structural Equation Modelling (PLS-SEM), which examined economic performance, financial management, and profitability. Findings - The instance indicates that the lack of organization-wide integrated systems, common across enterprises, contributes to this problem. The major issue is that the organization's information systems strategy never expressly prioritizes KM-enabling schemes. Practical Implications—The study's conclusions have major practical ramifications. Iraqi enterprises should prioritize resource optimization, cost control, and strategic financial planning to improve economic performance. In addition, governments should promote building projects through incentives, subsidies, and tax policies that boost economic productivity and profitability. These policies are available here. Originality/Value—This study adds to the literature by stressing economic performance as a mediator between financial management methods and profitability in Iraq's construction sector. It examines the dynamics of this link in Iraq's building sector. With the new data, firms may improve financial performance by making informed judgments and using efficient financial management procedures.